THE PHONOLOGICAL SYSTEM OF BALINESE LANGUAGE ON TEGALLINGGAH SPOKEN BY MOSLEM PEOPLE: A DESCRIPTIVE QUALITATIVE STUDY - Naraswari, G.A.A.P.; Budasi, I.G.; Wedhanti, N.K. (Language and Education Journal Undiksha, 2018)
This synchronous study was designed in a descriptive qualitative form. This study was designed to describe the number of phonemes needed in the Tegallinggah dialect and its distribution. This study only supports segmental phonemes. Three informants from Tegallinggah Dialek were selected based on a set of predetermined standard requirements and criteria. Data was collected using two word lists namely: Swadesh and Nothofer. The data obtained were analyzed and collected descriptively. Tegallinggah Dialect has 44 phonemes and not all phonemes have a complete distribution (initial, middle and end positions). Phonemes can be played into: six vowels, nineteen consonants, five cluster consonants and 4 geminate, eight diphthongs.